1993
DOI: 10.3928/0098-9134-19931001-05
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENTAL PROCESS: Family Caregivers of Demented Japanese

Abstract: 1. Developmental process of caring for demented elders: the case of family caregivers consists of the beginning process (stage 1 through 4) and the awakening process (stage 5 through 7). 2. In the beginning process, the caregiver is unaware of the interaction between him/her and the demented family member, relies on conventional, general-purpose methods of care and on verbal communication, and consider care in terms of training and discipline of the person cared for. 3. The caregiver in the awakening process h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Over the past decade several studies have attempted to chart the ways in which caregiving   (  ) changes over time, resulting in so-called 'temporal' models which try to identify key transitions or points of change (see, for example, Kobayashi, Masaki, & Noguchi, 1993;Wuest, Ericson, & Stern, 1994;Aneshensel et al, 1995;Keady, 1999).These studies are not suggesting that all caregivers will follow a uniformly similar path -indeed, most are at pains to point out diversity. However, they do suggest that despite individual variation it is possible to identify 'threads of continuity' (Aneshensel et al, 1995) or to 'discern consistency' (Montgomery & Kosloski, 2000) which can provide 'markers' as to when is the best time to offer help and what help is likely to be most useful at a particular point in time (Montgomery & Kosloski, 2000).…”
Section: Services For Carers: All That Research and Still No Answers?mentioning
confidence: 99%
“…Over the past decade several studies have attempted to chart the ways in which caregiving   (  ) changes over time, resulting in so-called 'temporal' models which try to identify key transitions or points of change (see, for example, Kobayashi, Masaki, & Noguchi, 1993;Wuest, Ericson, & Stern, 1994;Aneshensel et al, 1995;Keady, 1999).These studies are not suggesting that all caregivers will follow a uniformly similar path -indeed, most are at pains to point out diversity. However, they do suggest that despite individual variation it is possible to identify 'threads of continuity' (Aneshensel et al, 1995) or to 'discern consistency' (Montgomery & Kosloski, 2000) which can provide 'markers' as to when is the best time to offer help and what help is likely to be most useful at a particular point in time (Montgomery & Kosloski, 2000).…”
Section: Services For Carers: All That Research and Still No Answers?mentioning
confidence: 99%
“…Such moments became the fuel of future caring commitment. 31 Family carers' continued involvement was justified to them in those brief moments, uplifting their spirits to continue on in their caring efforts knowing they were not in vain.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from other studies, particularly in relation to caregiving for the elderly, were similarly interpreted as culturally related. The availability of family support and help were critical in how caregivers coped with adults with dementia and who were mentally ill (Chiu, Shyu, Liu, Wang, & Chang, 2001;Kobayashi, Masaki, & Noguchi, 1993;Suwa-Kobayashi, Yuasa, & Noguchi, 1995;Yamamoto-Mitani, Tamura, Deguchi, Ito, & Sugishita, 2000) and the cultural values related to the meaning of family and illness were critical in understanding how families interpreted and coped with children who were mentally ill (Jung, 2000;). Chang (1999, 2000) found that caregiving tasks for cancer patients in Hong Kong were more difficult for younger caregivers because of their multiple family demands.…”
Section: Areas Of Content Focus (Questions 4 and 5)mentioning
confidence: 99%